Adjustable Magnetic-Control Design of a Metasurface for Sound Insulation - Xia, Pu; Lai, Yun; Liu, Xiaozhou (Frontiers in Mechanical Engineering, 2022)
Magnetic field is one efficient approach to realize non-contact control of materials. Here, we propose a type of membrane-based metasurface consisting of several parts of magnetorheological films embedded with magnetic particles, which enable non-contact control of sound insulation through magnetic field. The abundant degree of freedoms in membrane-type metamaterials are explored by considering composite structures. Through numerical calculations, we have investigated the effect of magnetic field excitation and film composition on the acoustic properties and the performance for sound insulation. We find an optimized model for better adjustability, wider acoustic band, and more balanced performance.